Visible Fists, Clandestine Kicks, and Invisible Elbows: Three Forms of Regulating Neoliberal Poverty - Auyero, Javier (European Review of Latin American and Caribbean Studies, 2010)
Argentina In a preliminary attempt to understand the daily production of poor people’s subordination in contemporary Argentina, this paper explores the workings of overt and covert forms of state violence against the urban destitute and of more subtle modes of domination. Attention to the simultaneous operation of what this paper calls visible fists, clandestine kicks, and invisible elbows in the daily life of the dispossessed serves to a) better integrate violence into the study of popular politics, and b) cast light on the productive (and not merely repressive) nature of state power.   Resumen: Puños visibles, patadas clandestinas y codos invisibles: tres formas de regulación de la pobreza neoliberal En un acercamiento preliminar a la producción cotidiana de la subordinación de los pobres urbanos en la Argentina contemporánea, este artículo explora las formas abiertas y encubiertas de violencia estatal contra los más destituidos y las modalidades más sutiles de dominación. Una atención simultánea a lo que el artículo denomina puños visibles, patadas clandestinas, y codos invisibles en la vida cotidiana de los desposeídos es útil a los efectos de: a) integrar la violencia en el estudio de la política popular, y b) iluminar la naturaleza productiva (y no meramente represiva) del poder estatal.